'You need to criticize, not just summarize!' Investigating 'Criticality' in written assignments of postgraduate students. (26th June 2018) - Mirador, Josephine
Abstract : Perhaps one challenge facing postgraduate students is the writing of essays responding to a specific reading assignment. Such an essay requires students not only to summarize, but to engage in a discussion of the significant points of the article, pointing out its strengths as well as its weaknesses. This paper presents the results of an investigation on criticality in written assignments of postgraduate students in applied linguistics and TESOL. It will discuss: How 'critical' are students when writing their assignments? What kind of 'critical' comments are they able to offer?Seventy assignments in the form of essays were analysed, using corpora from three universities in Asia (2010-2014). The investigation adopted a combination of quantitative and qualitative content analysis. In the quantitative phase, the commenting or critiquing sentences were identified and counted vis-à-vis reporting/summarizing information. In the qualitative phase, the critiquing or commenting parts were further analysed, and identified according to their functions or 'moves'. The initial findings from the investigation include: (1) the almost equal proportion of commenting/critiquing and summarizing/reporting information in the assignments; (2) the identification of four broad functions for the commenting or critiquing information adopted by students, each of which has a number of possible specific 'moves' or categories; (3) presence of critique 'nodes' as distinguished from 'support' comments; and (4) the identification of at least four moves as the most recurrent and possibly obligatory categories. This investigation has unearthed issues that are definitely worth investigating as extensions of this research, and will be of interest (most especially) to genre analysts and teachers of writing. Most of all, it will be of interest to postgraduate students in applied linguistics/TESOL programmes who may be wondering about the level of criticality they exhibit when writing assignments for their courses.